Determination of volatile organic compounds (VOCS) at selected pump stations in Johor Bahru - Hassim, Mimi Haryani (2015)
The determination of volatile organic compounds (VOCs) at selected pump stations in Skudai, Johor Bahru was investigated. About 27 chemicals substances in petrol and 24 chemicals substances in diesel with different concentration have been identified in each pump station. Benzene, toluene, ethylbenzene and xylene (BTEX) and MTBE have been chosen as VOCs of interests because of their toxicity properties that can gives hazardous to human health. The exposures of benzene at all three pump stations during refuelling the liquid fuel have potential to cause cancer riskwhile, ethylbenzene stated as acceptable risk to the people health.As for noncarcinogenic substances, the exposure of toluene, xylene and MTBE were recorded as acceptable risk to the people health at all the studied pump stations. Besides, there is a great correlation between physical environment factors; temperature, relative humidity and wind speed typically with total volatile organic compounds that evaporate into the ambient air during refuelling activities.